Uma arquitetura de data warehouse para apoio à gestão de projetos em desenvolvimento distribuído de software - Milanêz, Clara Aparecida (2010)
Project management involves decision-making, which must be based on solid, complete and consistent data. The complexity of the management may increase when it involves the design of distributed software development (DSD) and when there are many data that will be evaluated by a project manager and geographically dispersed. One solution is to gather and store project data in a data warehouse (DW) - that grows over time and stores the history, then to extract information to help planning and controlling projects with distributed development. To build a DW is necessary to define an architecture based on the end users needs - in this research of the DW users are the software project managers. This paper presents architecture for DW to support management project of DSD and describes the implementation of this architecture for the DW to DiSEN, a distributed software engineering environment created by the Study Group on Distributed Software Engineering, from State University of Maringá (UEM). The proposed architecture is architecture in layers for global DW, composed of incremental, subject-oriented data marts (DMs). To propose architecture, was needed to elicit requirements from the project managers of DSD and to identify the subject areas to be used as a basis for to implement of the DMs.